As relações dos professores formadores com os seus saberes profissionais - Junckes, Rosane Santana (2009)
This research aims to investigate the relation that teacher educators establish with their professional knowledge in licensure courses, and it starts with the presumption that such relations affect their activity in the universities. The theoretical foundation of this research are the studies developed by André (2008), Roldão (2007), Pereira (2006), Charlot (2005; 2001; 2000), Abdalla (2006), Pimenta and Anastasiou (2005), Lüdke (2004), Tardif (2008; 2002), Gómez (2001) among others who investigate the teacher education. The data were collected by both balancing the knowledge and recurrent interviews made with teacher educators of different areas of knowledge from licensure courses of a university in the South of Brazil. Such data show that the relation the teacher educators establish with their professional knowledge emerge mainly from the institutional culture, as much in the period prior graduation as in the professional socialization in the institutions in which they act professionally. In the university atmosphere the teacher educators establish relations of conflict with the specific and pedagogical knowledge, which generate convergence and divergence spots between the theory and the pedagogical practice and they implicate in the conception of the reflective/searching teacher. The study also shows that the teacher educators are apprehensive and disappointed with the deterioration of the image and the social status of their profession, which leads them to isolation and, in some cases, to professional frustration